The Effects of Switching Costs on Customers using Mobile Phone Services in Kenya - Muturi, Francis M. (Strathmore University, 2012)
This study investigated the effects of switching costs on customer value and ultimately customer loyalty among mobile phone service users in Kenya. In Kenya, there are over 28 million mobile phone subscribers by December, 2011, representing 71.3% penetration of the total population. In 2012, Kenya has four mobile phone service operators, who are engaged in a fight for customer numbers. Customers in the mobile telecommunication industry, have options to choose among a number of mobile phone service providers and actively put into effect their rights of switching from one service provider to another. The study used 400 university of Nairobi and Strathmore university students as surrogate users of mobile phone services in Kenya. The study adopted a quantitative research design. The primary data was collected using questionnaires which were administered by direct interaction with the respondents. The study established two critical factors that customer consider important while choosing a mobile phone services provider as encompassing perceived quality of service and perceived price. The study shows that significant differences exist between what customers expect from the service providers and what they perceive they experience after a service encounter. The study posits that there exists a positive relationship between customer perceived value and customer loyalty. Switching costs has a positive moderating influence on the relationship between customer perceived value and customer loyalty. This was interpreted to mean, an increase in switching cost will lead to an increase in customer perceived value and by proxy customer loyalty. The study shows, 79.8% of respondents have never used another service provider, with 19.6% indicating they have ever switched to another service provider. This immobility indicates a strong loyalty to mobile service providers and can be attributed to switching costs. Should customers decide to switch, 42.7% of the respondents could switch to Airtel and 42% to Yu, while Safaricom would be the greatest loser. Calling rates was the greatest reason for switching to other mobile phone service providers. This observation means that a mobile service provider who offers greater perceived customer value is likely to attract more loyal customers.
Submitted in partial fulfilment of the requirements for the Degree of Masters in Business Administration at Strathmore University
Keywords: Switching costs; Mobile phone service; Kenya